Labor demand - Hamermesh, Daniel S. 1943- (Princeton Univ. Press, 1993)
In this broad-ranging book, Daniel Hamermesh provides the first comprehensive picture of the disparate field of labor demand. The author reviews both the static and dynamic theories of labor demand, and provides evaluative summaries of the available empirical research in these two subject areas. Moreover, he uses both theory and evidence to establish a generalized framework for analyzing the impact of policies such as minimum wages, payroll taxes, job-security measures, unemployment insurance, and others. Covering every aspect of labor demand, this book uses material from a wide range of countries. Hamermesh also includes chapters on flows of employment through job creation and destruction in new and existing plants, the implications of labor demand for macroeconomics and the distribution of earnings, and the effects of heterogeneous labor for labor-market behavior in developing countries. For all labor economists, for graduate students specializing in the field of labor economics, for macroeconomists interested in public policy, and for public policy analysts interested in employment and pay, Labor Demand will be essential reading.
Literaturverz. S. [403] - 435
Keywords: Arbeidsmarkt; Demande (Théorie économique); Marché du travail; Trabajo - Oferta - Modelos matemáticos; Vraag en aanbod; Arbeitsmarkt; Labor demand; Labor market; Theorie; Arbeitsmarkttheorie; Arbeitsnachfrage